Hubungan Antara Self-Talk Positif dan Communication Apprehension Pada Mahasiswa BKI IAIN Parepare - emilia mustary (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2020)
This study aimed to see the relationship between the frequency of positive self-talk and the level of communication apprehension experienced by colege students.This study used a quantitative approach with a correlational design. The researchsample consisted of 75 students of the BKI IAIN Parepare Study Program, consisting of15 male and 70 female. The data collection technique by providing a scale in the formof the Self-talk Scale from Brinhaupt, Hein, and Kramer (2009) for measuring thefrequency of positive self-talk and the Personal Report of Communicationapprehension (PRCA) scale from McCroskey (1994) for measure communicationapprehension. The product moment analysis test is used to test the hypothesis byanalyzing the relationship between the frequency of doing positive self-talk and thelevel of communication apprehension. The results showed that there was a relationshipbetween the frequency of doing positive self-talk with the level of communicationapprehension among students with a significance value of 0.000 (p <0.05) and acorrelation coefficient value of -0.452. The more often students do positive self-talk, thelower level of communication apprehension they feel. The effective contribution givenby the positive self-talk variable to the communication apprehension variable was45.2%. The implication of this study shows that positive self-talk techniques can beused in improving students' personal competence in communication and can be appliedto various communication situations, including the guidance and counseling process.